Patients' Perspectives on Participation in an Effectiveness Study on Footwear Modification for the First Metatarsophalangeal Joint Osteoarthritis: A Qualitative Study - Carla Braam; Sabine Kloprogge; Dieuwke Schiphof; Joyce B. J. vanMeurs; Sita M. A. Bierma‐Zeinstra; Marienke vanMiddelkoop (Journal of Foot and Ankle Research, 2025)
ABSTRACT Background The effectiveness of footwear modifications for the first metatarsophalangeal (MTP) joint osteoarthritis (OA) compared to usual general practitioner (GP) care has never been studied. Understanding patients' perspectives is essential for assessing the feasibility of a randomized controlled trial (RCT) on this topic. Our objective is to explore experiences, expectations, beliefs, and opinions of patients with the first MTP joint OA regarding symptoms and limitations, healthcare management, footwear intervention, and research participation for designing a successful future effectiveness trial. Method A qualitative research design was embedded within a feasibility pilot study for the recruitment of participants diagnosed with the first MTP joint OA. Qualitative data from semistructured interviews were categorized analyzed. Results All participants (n = 10) experienced limitations on the activity and participation level due to pain symptoms in the first MTP joint. Patients experienced varying approaches and treatment outcomes in primary and secondary healthcare, leading to both positive and negative perspectives. Most participants highlighted the importance of the cosmetic appearance of modified footwear, indicating that this is crucial for compliance with the intervention. Participants showed willingness to participate in an RCT, with strong preference for randomization into an intervention group with a modified footwear alongside usual GP care rather than GP care alone. Conclusion Our study identified key considerations for designing a successful future trial, including recruiting incident cases, offering the deferred footwear intervention to the control group, providing clear information during recruitment and randomization phase, and the significance of the cosmetic appearance of modified footwear for patients with the first MTP joint OA.